Penerapan Alat Peniris Minyak Sentrifugal untuk Meminimalkan Kandungan Minyak pada Berbagai Macam Olahan Makanan pada Usaha Kecil Kuliner di Kelurahan Sekaran Gunungpati Semarang - Widjanarko, Dwi; Kusumaningtyas, Ratna Dewi; Yudiono, Heri; Kusumawardani, Rini; Widyastuti, Catur Rini (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Sekaran is a fairly densely populated area because it is located around the Semarang State University campus. With this dense population, culinary businesses around Sekaran are also growing. Many culinary businesses produce fried foods of various types. The problem encountered in this culinary business is that there is still a lot of oil content in the food products. This of course can harm the health of consumers. The aim of this activity is to reduce the oil content in food. The solution used is to apply an oil drainer to food products produced by culinary businesses around Sekaran. The activities carried out include: providing an understanding of the dangers of food that contains a lot of oil, providing an explanation of how to drain oil from food quickly, and providing training in the use of a drainer. The results of the activities that have been carried out are 1) providing an explanation of the function of each part of the drainer. oil in food; 2) socialize the importance of reducing the oil content in fried foods; 3) education about the effects caused by the presence of oil in food; and 4) training on how to use tools to drain oil from food has been carried out through demonstrations of tool use.